(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: Evaluation of the analgesia perioperative renal transplant of erector spinae plane (ESP) compared with PCA analgesia (patient-controlled analgesia) and adverse effects. Materials and Methods: A study on 60 patients with indications for kidney transplant surgery at the Center for Surgical Anesthesia - Viet Duc Hospital, randomly distributed into 2 groups of ESP and a control group. Results: Age, height, weight, BMI, diagnosis, ASA, drug dosage and anesthetic method had no difference between the two groups of ESP and PCA with p > 0.05. The time for the ESP group to first require analgesia in the group was 5.7 ± 2.45 hours, 1.76 ± 0.31 hours longer than the PCA group alone. 24-hour morphine consumption of ESP 5.8 ± 3.5mg compared with PCA alone: 13.3± 6.5mg statistically significant difference with p < 0.05. VAS scores at rest and movement of the group under anesthesia decreased statistically. Conclusion: ESP is an effective method of pain relief during and after surgery, reducing the dose of morphine and reducing the amount of morphine consumption. It is recommended to apply to enhance the effectiveness of postoperative pain relief.